Synaptic Homeostasis and Allostasis in the Dentate Gyrus Caused by Inflammatory and Neuropathic Pain Conditions - Wang, Rui-Rui; Wang, Yan; Guan, Su-Min; Li, Zhen; Kokane, Saurabh; Cao, Fa-Le; Sun, Wei; Li, Chun-Li; He, Ting; Yang, Yan; Lin, Qing; Chen, Jun (Frontiers in Synaptic Neuroscience, 2018)
It has been generally accepted that pain can cause imbalance between excitation and inhibition (homeostasis) at the synaptic level. However, it remains poorly understood how this imbalance (allostasis) develops in the CNS under different pain conditions. Here, we analyzed the changes in both excitatory and inhibitory synaptic transmission and modulation of the dentate gyrus (DG) under two pain conditions with different etiology and duration. First, it was revealed that the functions of the input-output (I/O) curves for evoked excitatory postsynaptic currents (eEPSCs) following the perforant path (PP) stimulation were gained under both acute inflammatory and chronic neuropathic pain conditions relative to the controls. However, the functions of I/O curves for the PP-evoked eIPSCs differed between the two conditions, namely it was greatly gained under inflammatory condition, but was reduced under neuropathic condition in reverse. Second, both the frequency and amplitude of miniature IPSCs (mIPSCs) were increased under inflammatory condition, however a decrease in frequency of mIPSCs was observed under neuropathic condition. Finally, the spike discharge of the DG granule cells in response to current injection was significantly increased by neuropathic pain condition, however, no different change was found between inflammatory pain condition and the control. These results provide another line of evidence showing homeostatic and allostatic modulation of excitatory synaptic transmission by inhibitory controls under different pathological pain conditions, hence implicating use of different therapeutic approaches to maintain the homeostasis between excitation and inhibition while treating different conditions of pathological pain.